Regenerative Tourism Model in Brastagi District: Integration of Local Wisdom, Agroecotourism, and Nature Conservation - DARYANA, Aditya pratama (Journal Management and Hospitality, 2024)
This research aims to design a regenerative tourism model in Brastagi District by integrating local wisdom values, agroecotourism practices, and community-based conservation approaches. The main problem raised is the lack of a tourism governance model that is able to answer the need to comprehensively improve socio- ecological conditions in mountainous agroecological areas. This research uses an exploratory qualitative method with a participatory case study approach. Data were obtained through in-depth interviews, participatory observations, focus group discussions, and document studies analyzed using grounded theory techniques. The results of the study show that local values such as customary deliberation and mutual cooperation play a role as the foundation of inclusive governance, while agroecological practices and customary forest conservation can be used as educational and ecological tourism attractions. The conceptual model built reflects the integration of social, agricultural, and natural systems that support each other in creating tourist destinations that are not only sustainable but also able to regenerate the environment and improve the welfare of local communities. The conclusion of the study states that regenerative tourism can be a strategic approach in designing a more equitable and resilient tourism future in rural areas. These findings open up space for the replication of the model in other regional contexts with similar characteristics and serve as the basis for policy advocacy and the development of locally-based regenerative tourism success indicators.